Labile carbon fractions build-up and dynamiccs under vertical stratification of Populus deltoides and Eucalyptus tereticornis based agroforestry systems in Trans-Gangetic Plains of India - Chaudhari, S.K.; Kumar, Praveen; Mishra, Ajay Kumar; Singh, Kailash; Rail, Poornima; Singh, Rakesh; Sharma, D.K. (Annals of Agricultural Research, 2016)
Populus deltoides and Eucalyptus tereticornisn based agroforestry systems are credited for stocking  significant amounts of soil carbon and hence have the potential to mitigate climate change. In this study, Four different lands uses were compared in terms of labile carbon fractions build up in varying soil depth. Soil Organic Carbon under 4-year Populus and Eucalyptus based agroforestry system was 22.9 and 6.30% higher respectively than sole wheat crop. Microbial biomass carbon under 4-year Populus and Eucalyptus based agroforestry system was 10.6 and 12.3% higher than sole wheat crop. Permanganate Oxidizable Carbon under 4-year Populus and Eucalyptus based agroforestry system was 4.4 and 23.1% higher than sole wheat crop.In Populus and Eucalyptus based agroforestry system,significant positive correlation were recorded between POXC and MB-C(r=0.809** and 0.889**) POXC and SOC(r=903** and 0.793**) and SOC and MB-C (r=0.765** and 0.852**) respectively.The relationship between POXC and SOC under Populus (4-year)+wheat(R2=0.845) had stronger relationship than Eucalyptu s(4-year)+wheat(R2=0.712). This study demostrated the usefulness of POXC in assessing changes in the liable soil C pools quickly and inexpensively under Populus and Eucalyptus based agroforestry systems in Trans-Gangetic plains of India.